CLINICAL AND DERMOSCOPIC FEATURES OF SKIN CANCER AT SANGLAH GENERAL HOSPITAL, DENPASAR: A CASE SERIES STUDY - Made Wardhana; Nila Puspasari; Prima Sanjiwani; Darmaputra Darmaputra (Journal of Global Pharma Technology, 2017)
Background: Dermoscopy or epiluminescence microscopy (ELM) is a non-invasive clinical examination technique of pigmented skin lesions and early stage skin cancers.Methods: This was a retrospective study of patients with skin cancer at dermatology outpatient clinic of Sanglah Hospital from January 2013 to December 2014. These patients were firstly assessed with unaided eye before underwent a dermoscopic examination. All diagnoses were confirmed with a histopathology examination.Results: There were 22 patients with skin cancer who enrolled in this study. The study participants were redominantly women (59.1%), age over 50 years (72.7%), working outdoor (90.9%), with the predominantly predominant site being on the face (96%). There were 7 patients (31.8%)  with malignant melanoma and the predominant dermoscopic features were: atypical pigment network (71.4%), blue whitish veil (57.1%) and irregular streaks (57.1%). There were 10 patients (45.5%) with basal cell carcinoma, with the predominant dermoscopic feature being the arborizing vessel (60%) and ulceration (70%). There were 5 squamous cell carcinoma patients (22.7%) and the predominant dermoscopic features observed were keratin (80%) and hairpin vessels (100%). The histopathological examination results were in accordance with the description of dermoscopy featuresConclusions: Dermoscopy is a non-invasive tool for diagnosis of early skin cancer prior to performing a biopsy for histopathologic examination.